Influence of storage temperature on lipid oxidation kinetics and quality stability of snakehead fish (Channa striata) sausages - Sri Iriyanti; Budi Kristanto; Nia Budhi Astuti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Lipid oxidation is the primary cause of quality deterioration in fish-based products, with malondialdehyde (MDA) accumulation posing implications for sensory quality and food safety. This study evaluated the effect of storage temperature on lipid oxidation kinetics in snakehead fish (Channa striata) sausage over 30 d. Room temperature (25 ± 3 °C) and cold storage (10 ± 2 °C) were applied to nine independent samples each. Lipid oxidation was quantified as thiobarbituric acid reactive substances (TBARS) on days 0, 5, 10, 15, 20, 25, and 30, and zero- and first-order kinetic models were evaluated. TBARS increased under both conditions, reaching 0.376 mg MDA/kg at 25 °C and 0.178 mg MDA/kg at 10 °C on day 30, both of which were below the sensory rancidity threshold. Storage temperature, time, and their interaction significantly affected TBARS (p < 0.001; η² = 0.79, 0.85, 0.53). The first-order model fit better at 25 °C (R² = 0.996; k = 0.0598 d ⁻¹), and the zero-order model fit better at 10 °C (R² = 0.981; k = 0.0350 d ⁻¹). The Arrhenius activation energy was measured to be 25.11 kJ/mol. Cold storage reduced the oxidation rate by approximately 41% compared to room temperature, making it a practical option for slowing lipid oxidation in snakehead fish sausage during short-term storage.